(untitled) (Web of Teachers: Inderscience Research, 2024)
Globalization has had a tremendous impact on language teaching, changing trends in curriculum design, pedagogy, and learning objectives. This article investigates the effects of globalization on language teaching, using data from a variety of scholars and experiments. It emphasizes important trends such as the growing dominance of English, the rise of multilingualism, and the incorporation of technology. The article demonstrates how globalization has created both opportunities and challenges in language instruction using key examples and research-based information.